Prevalence and Factors Associated with Frailty Among Peruvian Older Adults - Runzer Colmenares, Fernando M. (2014)
The objective of this study is to examine the prevalence and factors associated with frailty in Peruvian Navy Veteran's older adults and family members. A total of 311 non-institutionalized men and women aged 60 years and older, from the Geriatrics Service of the Peruvian Navy Medical Center (Centro Médico Naval “Cirujano Mayor Santiago Távara”) were assessed between May and October 2010. Frailty was defined as having two or more of the following components: 1) unintentional weight-loss, 2) weakness (lowest 20% in grip-strength), 3) self-reported exhaustion, and 4) slow walking speed (lowest 20% 8-meter walk-time in seconds). Additionally, information on socio-demographic factors, medical conditions, depressive symptoms, disability, and cognitive function were obtained. Of the 311 participants, 78 (25.1%) were not frail, 147 (47.3%) were pre-frail, and 86 (27.8%) were frail. Using logistic regression analysis, we found that older age, being married, falls in the last year and disability were factors significantly associated with being frail. We conclude that prevalence of pre-frail and frail status in Peruvian Navy Veterans and family members is high. Our data reports risk factors for frailty that have been reported in the past in other population groups. A larger sample and longitudinal follow-up are needed to design and implement comprehensive geriatric interventions that can benefit Peruvian Navy Veteran's older adults at risk of becoming frail.